The pricing of subprime mortgage risk in good times and bad: evidence from the ABX.HE indices - Ingo Fender; Martin Scheicher (European Central Bank (ECB), 2009)
This paper investigates the market pricing of subprime mortgage risk on the basis of data for the ABX.HE family of indices, which have become a key barometer of mortgage market conditions during the recent financial crisis. After an introduction into ABX index mechanics and a discussion of historical pricing patterns, we use regression analysis to establish the relationship between observed index returns and macroeco-nomic news as well as market based proxies of default risk, interest rates, liquidity and risk appetite. The results imply that declining risk appetite and heightened concerns about market illiquidity - likely due in part to significant short positioning activity -have provided a sizeable contribution to the observed collapse in ABX prices since the summer of 2007. In particular, while fundamental factors, such as indicators of housing market activity, have continued to exert an important influence on the subordinated ABX indices, those backed by AA and AAA exposures have tended to react more to the general deterioration of the financial market environment. This provides further support for the inappropriateness of pricing models that do not sufficiently account for factors such as risk appetite and liquidity risk, particularly in periods of heightened market pressure. In addition, as related risk premia can be captured by unconstrained investors, ABX pricing patterns appear to lend support to government measures aimed at taking troubled assets off banks' balance sheets - such as the US Troubled Asset Relief Program (TARP) in its original form.
Keywords: E43; G12; G13; G14; 330; ABX index; mortgage-backed securities; pricing; risk premia; Asset-Backed Securities; Subprime-Krise; Risikoprämie; Prognoseverfahren; Indexberechnung; USA